Analysis of Soil from the Black Sea Region of Northern Turkey Using Energy Dispersive X-Ray Fluorescence Spectrometry - Ekinci, R.; Dogan, B.; Ekinci, N.; Bilyeu, B.; Jones, R. (Asian Journal of Chemistry, 2012)
This study, examines trace element analysis of eighteen soil samples taken from the provinces of Trabzon and Giresun. The concentrations of trace elements were determined using energy dispersive X-ray fluorescence. The physical basis of the analytical method used, experimental set up and the sample preparation are described. X-ray spectra were collected using a Si(Li) detector with a Camberra DSA-1000 desktop spectrum analyzer and Am241 and Fe55 annular radioactive sources. The energy resolution of the spectrometer is 160 eV at 5.9 keV.